Evidence of an Antimicrobial Peptide Signature Encrypted in HECT E3 Ubiquitin Ligases - Candido-Ferreira, Ivan Lavander; Kronenberger, Thales; Sayegh, Raphael Santa Rosa; Batista, Isabel de Fátima Correia; da Silva Junior, Pedro Ismael (Frontiers in Immunology, 2017)
The ubiquitin-proteasome pathway (UPP) is a hallmark of the eukaryotic cell. In jawed vertebrates, it has been co-opted by the adaptive immune system, where proteasomal degradation produces endogenous peptides for major histocompatibility complex class I antigen presentation. However, proteolytic products are also necessary for the phylogenetically widespread innate immune system, as they often play a role as host defense peptides (HDPs), pivotal effectors against pathogens. Here, we report the identification of the arachnid HDP oligoventin, which shares homology to a core member of the UPP, E3 ubiquitin ligases. Oligoventin has broad antimicrobial activity and shows strong synergy with lysozymes. Using computational and phylogenetic approaches, we show high conservation of the oligoventin signature in HECT E3s. In silico simulation of HECT E3s self-proteolysis provides evidence that HDPs can be generated by fine-tuned 26S proteasomal degradation, and therefore are consistent with the hypothesis that oligoventin is a cryptic peptide released by the proteolytic processing of an Nedd4 E3 precursor protein. Finally, we compare the production of HDPs and endogenous antigens from orthologous HECT E3s by proteasomal degradation as a means of analyzing the UPP coupling to metazoan immunity. Our results highlight the functional plasticity of the UPP in innate and adaptive immune systems as a possibly recurrent mechanism to generate functionally diverse peptides.